Modelling harvesting animal population at high school with spreadsheets – the case of Moby Dick - Jan Benacka; Sona Ceretkova (McMaster University, 2014)
The paper gives the results of an experiment in which harvesting the world population of the Sperm whale was modelled and analyzed with 27 high school students of age 18-19 by using the Euler method of solving differential equations in Excel. A questionnaire survey was carried out to find out the opinion of the students of the lesson. The results are discussed.